PERLINDUNGAN HUKUM TERHADAP KONSUMEN PT. PLN (PERSERO) PEKANBARU RAYON KOTA BARAT DALAM KASUS PEMUTUSAN LISTRIK - Triani, Yeni; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
PT. PLN (Persero) is a state-owned electricity company that has contributed a great deal in supplying electricity to the community, because most of the community's needs depend heavily on electricity. Then it cannot be denied that electricity is needed by society. Regulations whose material protects the interests of consumers and business actors, namely Law No. 30 of 2009 concerning Electricity. In Article 1 paragraph (10) of the Electricity Law, the relationship between electricity consumers and users of electricity services with the PT. PLN is the sale and purchase of electricity which is regulated in the Electricity Sale and Purchase Agreement (SPJBTL). But if observed in reality there are still consumers of PT. PLN (Persero) Area of Pekanbaru City that does not receive electricity services properly. Constraints that are still faced in the electricity sector that harm consumers include information on electricity outages of PT. PLN (Persero) Area of Pekanbaru City which is less known or understood by consumers. Power outages in the area of Pekanbaru City cause losses to consumers in the form of material and immaterial losses.This research is a field research that is direct research that the authors do intensively, in detail and deeply at PT. PLN (Persero) Area of Pekanbaru City. Data collection methods used in this study were observation, interviews with informants and questionnaires distributed to customers of PT. PLN (Persero) Area of Pekanbaru City. The legal effort that can be taken by consumers who feel disadvantaged is to choose to directly take legal action to the office of PT. PLN (Persero) Area of Pekanbaru City.Keywords: Consumer, Protection, Law, Electricity